(untitled) (Khairulummah, 2022)
Abstract Islamic Sharia’s is the main source of guidance in all fields of human life. The Prophet ﷺ put the foundation of all systems in the light of Allah’s orders. The Rashidun caliphs tried hard to improve these systems in their respective eras۔ The era of the first caliph Abu Bakr Siddiq was spent in the midst of apostasy and the denial of zakat. While religion was strengthened during Umar Farooq’s reig۔ during his time, he established the Police Department, Zakat Department and Agriculture Department and presented organized systems based on strong laws. The objectives of the economic system of Islam include the eradication of poverty and the provision of equal economic opportunities to all human beings۔ Islam emphasizes the creation of strategies that will eradicate poverty and fulfill the basic needs of all human beings۔ In this article under review, the importance and rules of the most important member of the economic system "Agriculture" will be explained and then Umar’s agricultural reforms will be reviewed.